Pemberdayaan UMKM Tempe dan Kerupuk Aci melalui Legalitas Usaha Di Desa Randusanga Wetan, Kabupaten Brebes - Angga Saddam S; Hendri Sucipto; Amelia Sholeha; M. Badrun Zaman (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2023)
The government is committed to empowering Micro, Small and Medium Enterprises (MSMES) in Indonesia, MSMES are a form of small business whose existence plays a very important role in empowering the community to have independence in the economic sector. MSMEs that are used as partners in community service activities are people who are members of the home industry in the village of Randusanga Wetan, Brebes Regency. This article at least describes the results of the community service process carried out by the community service team from Muhadi Setiabudi University, Brebes, offering assistance services on the importance of business legalization so that it can be more competitive globally. Having a business license is very important for the community, but sometimes there are not a few people who don't want to take care of their business license due to lack of knowledge, limited data, and so on. Through this community service activity, the goals and targets to be achieved in community service activities are business legalization for MSME actors. By having business legality, business actors are expected to be able to compete in the free market era. The method used in this service activity is carried out in the form of counseling and assistance in managing business legality